Formation of ST12 phase Ge nanoparticles in ZnO thin films. (December 2015) - Ceylan, Abdullah; Gumrukcu, Ali E.; Akin, Nihan; Ozcan, Sadan; Ozcelik, Suleyman
Abstract: In this work, we focus on the Ge nanoparticles (Ge-np) embedded ZnO multilayered thin films. Effects of reactive and nonreactive growth of ZnO layers on the rapid thermal annealing (RTA) induced formation of Ge-np have been specifically investigated. The samples were deposited by sequential r.f. and d.c. sputtering of ZnO and Ge thin film layers, respectively on Si substrates. As-prepared thin film samples have been exposed to an ex-situ RTA at 600 °C for 60 s under forming gas atmosphere. Structural characterizations have been performed by X-ray Diffraction (XRD), Raman scattering, Secondary Ion Mass Spectroscopy (SIMS), and Scanning Electron Microscopy (SEM) techniques. It has been realized that reactive or nonreactive growth of ZnO layers significantly influences the morphology of the ZnO: Ge samples, most prominently the crystal structure of Ge-np. XRD and Raman analysis have revealed that while reactive growth results in a mixture of diamond cubic (DC) and simple tetragonal (ST12) Ge-np, nonreactive growth leads to the formation of only DC Ge-np upon RTA process. Formation of ST12 Ge-np has been discussed based on structural differences due to reactive and nonreactive growth of ZnO embedding layer.